Experiences of caregivers desiring to refuse life-prolonging treatment for their elderly parents at the end of life. Issue 1 (1st January 2019) - Maura, Yuki; Yamamoto, Mariko; Tamaki, Tomoko; Odachi, Ryo; Ito, Mikiko; Kitamura, Yuri; Sobue, Tomotaka
ABSTRACT: Purpose : This study aimed to clarify the experiences of caregivers desiring to refuse life-prolonging treatment for their elderly parents at the end of life. Methods : A semi-structured interview was performed for four family caregivers who wanted to refuse life-prolonging treatment suggested by the physicians. Results : In this study, four caregivers who refused life-prolonging treatment suggested by the physicians for their elderly parents completed semi-structured interviews. The obtained data were analyzed in relation to the theme "Experiences of caregivers who desire to refuse life-prolonging treatment for their elderly parents at the end of life." As a result, 38 subcategories and 12 categories were extracted. Conclusions : Participants in this study initially had a negative view of life-prolonging treatment. However, they agonized over the decision when they received conflicting advice from the physicians. The participants indicated that physicians' advice and attitudes complicated their decisions to reject life-prolonging treatment for their elderly parents.